2017
DOI: 10.1093/bib/bbx151
|View full text |Cite
|
Sign up to set email alerts
|

Systems Bioinformatics: increasing precision of computational diagnostics and therapeutics through network-based approaches

Abstract: Systems Bioinformatics is a relatively new approach, which lies in the intersection of systems biology and classical bioinformatics. It focuses on integrating information across different levels using a bottom-up approach as in systems biology with a data-driven top-down approach as in bioinformatics. The advent of omics technologies has provided the stepping-stone for the emergence of Systems Bioinformatics. These technologies provide a spectrum of information ranging from genomics, transcriptomics and proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 200 publications
0
78
0
1
Order By: Relevance
“…In one example, additional information on urine organic acid analysis was derived that could inform on treatment compliance [82]. Data generated from semi-targeted LC-MS/MS platforms could also be interrogated [54,56], were this to be linked with data on new diagnoses made through other methods, such as genomics [83]. The power here rests with creating linked datasets and bi-directionally mining them, as a form of systematic examination.…”
Section: Biomarker Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…In one example, additional information on urine organic acid analysis was derived that could inform on treatment compliance [82]. Data generated from semi-targeted LC-MS/MS platforms could also be interrogated [54,56], were this to be linked with data on new diagnoses made through other methods, such as genomics [83]. The power here rests with creating linked datasets and bi-directionally mining them, as a form of systematic examination.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…The power here rests with creating linked datasets and bi-directionally mining them, as a form of systematic examination. As with the advent of untargeted genomic testing (whole exome and genome sequencing), untargeted and semi-targeted metabolomic approaches provide a platform for the development of new disease biomarkers in situ [84], that is development, validation and repurposing for new clinical purposes while continuing to measure them for their existing intentions [83]. This underpins the notion for rapid translation from research into practice.…”
Section: Biomarker Discoverymentioning
confidence: 99%
“…SB is an interdisciplinary field which combines the research fields of systems biology and bioinformatics. SB allows the integration of biological data across the omics categories such a genomics, transcriptomics, proteomics, metabolomics, lipidomics, epigenomics and several types of omics data [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…del Rio et al (2009) by analyzing 16 well-known centrality measures demonstrated that while identification of network hubs based on a single centrality measure is not statistically significant, the combination of two centrality measures that involve both local and global features of the network could more reliably predict the most influential nodes (del Rio et al, 2009). In systems biology studies, nodes with high degree and betweenness centrality are usually represented as network hubs in the context of defining both local significance and global network flow (Fu et al, 2015;Oulas et al, 2019). However, no method or algorithm has been developed to date that integrates these centrality measures with the purpose of synergizing their effects.…”
Section: Introductionmentioning
confidence: 99%